By the Shallow Rivers of Babylon: Musical Mashups and the Sound of Lost Music in The Merry Wives of Windsor - Wylde, Jacqueline (Renaissance and Reformation / Renaissance et Réforme, 2024)
In The Merry Wives of Windsor, there is a humorous sound-based musical moment in act 3, scene 1 that no longer resonates with contemporary audiences; the sounds evoked in the text and intended for performance on the stage have become obsolete. This article begins by investigating the original sounds and meanings of the sonic moment in the play, exploring what they would have sounded like and what they meant to an Elizabethan audience. It then turns to three twentieth- and twenty-first-century productions that have contended with this outdated sonic moment in funny, memorable, and very different ways, asking how new productions can harness new sounds to capture old meanings.